Modeling of small hydro power plants - Özbay, Ebru; Genço?lu, Muhsin Tunay (My University, 2010)
Importance of small hydroelectric power plants has been increased more and more because of fast increasing electrical energy demand. Small hydro power plants have great importance caused by their low administrative, executive costs, using water drink and irrigation systems suitability for rural areas and low environmental effects. Hence, operation conditions and constructible possibilities of the plants must be determined. In this study, the role of small hydroelectric power plants has been investigated. In order to carry out load-frequency control of small hydroelectric power plants in computer, the models of turbine, generator, and governor have been generated. After small hydroelectric power plant model has been obtained by being combined these models. Hydroelectric power plant models having linear turbine have been acquired the variations of power and frequency with respect to time by being operated for different load values.
Küçük hidroelektrik santrallerin modellenmesi
2010 7th National Conference on Electrical, Electronics and Computer Engineering, ELECO 2010 -- 2 December 2010 through 5 December 2010 -- Bursa -- 83834
Keywords: Electrical engineering; Energy management; Hydroelectric power; Rural areas; Small power plants; Turbines; Electrical energy demand; Environmental effects; Irrigation systems; Load-frequency control; Operation conditions; Small hydro power plants; Hydroelectric power plants